Wear Resistance of Light-Cure Resin Luting Cements for Ceramic Veneers - Miyuki Oshika; Takafumi Kishimoto; Taku Horie; Abdulaziz Alhotan; Masao Irie; Veronica C. Sule; Wayne W. Barkmeier; Akimasa Tsujimoto (Journal of Functional Biomaterials)
The purpose of this study was to compare the wear resistance of light-cure resin luting cements for veneers with that of other luting materials investigated in earlier studies. An Alabama wear-testing machine was used to measure the wear resistance of four recent light-cure resin luting cements for veneers (G-Cem Veneer; Panavia V5 LC; RelyX Veneer Cement; and Vario-link Esthetic LC). The volume loss ranged from 0.027 ± 0.003 to 0.119 ± 0.030 mm3, the mean facet depth from 56.053 ± 7.074 to 81.531 ± 7.712 µm, and the maximum facet depth from 100.439 ± 26.534 to 215.958 ± 27.320 µm. G-Cem Veneer showed significantly better (p < 0.05) wear resistance than the other materials tested. Representative SEM images were obtained which showed differences in form among the wear facets for the luting cements examined. Correlations were calculated between the three measurements for each material, and the pattern of correlations was also different for each material.